SIMULTANEOUS ONSET OF HERPES ZOSTER IN A FATHER AND SON - Raza, Naeem; Dar, Nasser Rashid; Ejaz, Amer (Journal of Ayub Medical College Abbottabad, 2006)
The Varicella Zoster virus persists in sensory nerve ganglion cells after chicken pox and gets reactivated to cause herpes zoster after variable periods of time as a result of waning of specific cellular immunity. Susceptible contacts of herpes zoster can develop chicken pox and very rarely herpes zoster. We report an interesting case of a father and his son who developed herpes zoster simultaneously without any obvious common predisposition and discuss the possible underlying mechanism. Key Words: Herpes zoster, Simultaneous onset, Incubation period, Family.